Migration of digital functional capacity assessments from device resident to cloud-based delivery: Development and convergent validity - Philip D. Harvey; Richard S.E. Keefe; Peter Kallestrup; Sara J. Czaja; Hans Klein; William Horan (Schizophrenia Research: Cognition)
Decentralized clinical trials are leading to rapid changes in assessment technology, including an expansion of interest in remote delivery. As technology changes, some of the updates include migration to fully cloud-based software and data management, with attendant differences in hardware, response modalities, and modifications in the level of tester engagement. It is rare to see systematic descriptions of the process of migration and upgrading of technology-related assessments. We present comparative data on successive generations of two widely used functional capacity measures, the Virtual Reality Functional Capacity Assessment Tool (VRFCAT) and the Functional Capacity Assessment and Training System (FUNSAT). Four samples of healthy older individuals completed either the original device-resident, computer-administered versions, or cloud-based, tablet-delivered versions of these tasks. For the VRFCAT, performance and correlations with age were similar across versions, although performance was slightly (5 %) faster with iPad delivery. For the FUNSAT, performance and correlations with age and cognitive task scores were generally similar across versions for English Speakers, though there were some differences related to the testing language for the cloud-based version. These results support the feasibility of migrating digital assessments to cloud-based delivery and substantiate fundamental similarity across delivery strategies.